Political Interests and the Common Goods in Public Religion - Amin, Harris Usman; Darwin, Muhadjir; Ikhwan, Hakimul; Syamsiyatun, Siti (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This research explores the Gerakan Salat Subuh Berjamaah (GSSB)/Dawn Congregation Prayer Movement in the city government of Palembang. This policy using religious instruments has been implemented for approximately four years and has received recognition and appreciation from several parties for its benefits to the people and government of Palembang city. This research is qualitative research with a case study method, conducted for three months in Palembang City. The study results conclude that the GSSB policy created a public religion where religion enters the public sphere to fulfil the political actor's political interests (Mayor) and realize the â€œcommon goodsâ€ of Palembang city.